High-Frequency Transformation, by Electroporation, of Lactococcus lactis subsp. cremoris Grown with Glycine in Osmotically Stabilized Media - Holo, Helge (1989)
An efficient method for genetic transformation of lactococci by electroporation is presented. Highly competent lactococci for electrotransformation were obtained by growing cells in media containing high concentrations of glycine and 0.5 M sucrose as the osmotic stabilizers. These cells could be stored at −85°C without loss of competence. With Lactococcus lactis subsp. cremoris BC101, a transformation frequency of 5.7 × 10(7) transformants per μg of pIL253 DNA was obtained, which represents 5% of the surviving cells. All the lactococcal strains tested could be transformed by the present method.